Polemics and Political Situation in Cirebon Ahead of The Mayoral Election & Mayoral Candidate of Cirebon - Nurjanah, Aisyah; Amelia, Amelia; Ningsih, Widia (Sekolah Tinggi Agama Islam Kuningan, 2024)
This research discusses polemics and political dynamics in Cirebon ahead of the 2024 Cirebon Mayor and Mayor Candidate General Election. As part of the democratic process, the general election in Cirebon presents a fierce competition between candidates driven by local political interests and the influence of elite groups. The study aims to identify the factors that cause tension and competition in these elections and to explore their impact on local communities. The method used was qualitative descriptive with purposive sampling, in-depth interviews, and participatory observation. The results of the study revealed that the